Control de bienes y su influencia en la eficiencia y efectividad del manejo de materiales en la oficina técnica y de prestación de servicios Los Ríos del Ministerio de Desarrollo Urbano y Vivienda - Criollo Guaman, Soledad (2021)
The Ministry of Urban Development and Housing, known as MIDUVI, is a state entity, which is dedicated to guaranteeing that the citizens of the different cities and provinces have access to a safe and healthy habitat, also access to decent housing and to have a public space that is inclusive, this being the company chosen as the study entity to carry out the present case study. The present final work to obtain the title of Engineering in Accounting and Auditing of the Technical University of Babahoyo, under the name of a case study, called as: "CONTROL OF ASSETS AND ITS INFLUENCE ON THE EFFICIENCY AND EFFECTIVENESS OF THE HANDLING OF MATERIALS IN THE TECHNICAL OFFICE AND SERVICE DELIVERY LOS RIOS OF THE MINISTRY OF URBAN DEVELOPMENT AND HOUSING ”, has the purpose of making a critical observation to the processes of control of the goods and how they affect the effectiveness and efficiency of the institution. Thus, within the research carried out, a quantitative research method has been used, since the interview and observation are used as tools to know what are the problems in the processes of the Department in charge of the Assets within the entity .